2015
DOI: 10.1177/1756285615584739
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous immunoglobulin in treating inflammatory neuromuscular disorders

Abstract: Our results suggest that subcutaneous immunoglobulins can be an attractive alternative therapy in autoimmune neuromuscular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
(51 reference statements)
2
18
0
1
Order By: Relevance
“…In the study by Markvardsen et al, 20 of 29 (70%) CIDP patients who switched from IVIg to SC‐Ig preferred to continue with SC‐Ig at the end of the study, even though they experienced a larger proportion of mild and local adverse effects . Similar results were reported by other authors . Of interest, patients were similarly satisfied with IVIg as compared to SC‐Ig when both were administered at home .…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In the study by Markvardsen et al, 20 of 29 (70%) CIDP patients who switched from IVIg to SC‐Ig preferred to continue with SC‐Ig at the end of the study, even though they experienced a larger proportion of mild and local adverse effects . Similar results were reported by other authors . Of interest, patients were similarly satisfied with IVIg as compared to SC‐Ig when both were administered at home .…”
Section: Discussionsupporting
confidence: 67%
“…A recent cost‐minimization analysis performed in Italy found that the cost of either treatment, despite being lower for SC‐Ig, was only slightly different . The need for administration in a clinic or hospital setting, premedication, and a higher frequency of systemic adverse effects with IVIg may favor the lower cost of SC‐Ig . Cost was not considered in detail in this study, but deserves attention when analyzing both alternatives.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Within this short observation period, an equivalent efficacy of SCIg was demonstrated in these patients . Apart from these two studies there are case series and case reports of classes III and IV evidence [Bayas et al 2013;Cocito et al 2013;Köller et al 2006;Lee et al 2008;Markvardsen et al 2015], which also provide data that corroborate the utility of SCIg in patients with CIDP; one, even as a long-term clinical follow up [Yoon et al 2015]. The switch was due to various reasons such as stabilization by IVIg only, with short treatment intervals, side effects associated with IVIg therapy (e.g.…”
Section: Subcutaneous Immunoglobulins In Cidpmentioning
confidence: 99%
“…Equivalent clinical efficacy of SCIg after switching from IVIg was demonstrated in these patients as well, based on data gathered in the short 16-week observational period . Additional smaller case series or case reports emphasize the potential efficacy of SCIg in patients with MMN [Dacci et al 2010;Eftimov et al 2009;Hadden and Marreno, 2015;Köller et al 2006;Markvardsen et al 2015;Misbah et al 2011;Yoon et al 2015]. The switches from IVIg to SCIg were performed for the same reasons as mentioned in the reports in CIDP.…”
Section: Subcutaneous Immunoglobulins In Mmnmentioning
confidence: 99%